1998
DOI: 10.1111/1467-9663.00029
|View full text |Cite
|
Sign up to set email alerts
|

Do Networks Matter for Innovation? The usefulness of the economic network approach in analysing innovation

Abstract: Economic network theory emphasises the importance of external resource mobilisation. In this paper, the relations between the mobilisation and use of internal and external resources in innovation processes, and the innovative performance of ®rms, are explored empirically, using an adapted version of Ha Êkansson's (1987) economic network model. The main research question was: to what extent do network variables contribute to the innovative performance of ®rms? To answer this question, we assessed the explanator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
1
19

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(129 citation statements)
references
References 4 publications
7
102
1
19
Order By: Relevance
“…An innovation production function is used to model the effect of different kinds of knowledge sourcing on firms" probability of innovating. It describes the relationship between the propensity of a firm to innovate and a range of explanatory factors (Griliches 1979;Oerlemans et al 1998;Roper 2001;Janz, Lööf and Peters 2003;Love and Mansury 2007). Equation (1) presents the innovation production function to be estimated:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An innovation production function is used to model the effect of different kinds of knowledge sourcing on firms" probability of innovating. It describes the relationship between the propensity of a firm to innovate and a range of explanatory factors (Griliches 1979;Oerlemans et al 1998;Roper 2001;Janz, Lööf and Peters 2003;Love and Mansury 2007). Equation (1) presents the innovation production function to be estimated:…”
Section: Methodsmentioning
confidence: 99%
“…Whether the firm is indigenous or foreign owned may play a role in explaining innovation performance, which is an issue of particular relevance to Ireland given its reliance on foreign direct investment (Jordan and O"Leary 2008;Roper et al 2008) Similarly, the sector in which a firm operates may impact on its likelihood of innovation (Pavitt 1984;Oerlemans et al 1998). …”
Section: Knowledge Proximity and Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…This distinction is important since research has shown that different types of innovativeness are influenced by different types of resources (e.g. Oerlemans et al 1998). In this paper newness of innovation is defined by three categories, namely, products that are improved versions of products that were already produced by the firm, products that are new to the firm, and products that are new to the firm's market as a whole.…”
Section: Firm Innovativenessmentioning
confidence: 99%
“…Innovation is a socially-embedded process, where relationships and social activity and exchange are noted to be driving factors of innovative thinking and activity (Oerlemans, Meeus, and Boekena, 1998;Landry, Amar, and Lamari, 2002;Akcomac and ter Weel, 2008). Where the literature argues social capital's positive contribution to innovation as well as its adversarial effects -due to the formation of insular groups that prevent access to new information and diverse communities (Florida, Cushing, and Gates, 2002;Dakhil and De Clercq, 2004), social capital is still noted to mediate the access to information and experiences that affect innovative activity.…”
Section: Introductionmentioning
confidence: 99%